AhR activation increases IL‐2 production by alloreactive CD4+ T cells initiating the differentiation of mucosal‐homing Tim3+Lag3+ Tr1 cells. Issue 11 (15th September 2017) - Ehrlich, Allison K.; Pennington, Jamie M.; Tilton, Susan; Wang, Xisheng; Marshall, Nikki B.; Rohlman, Diana; Funatake, Castle; Punj, Sumit; O'Donnell, Edmond; Yu, Zhen; Kolluri, Siva K.; Kerkvliet, Nancy I.
Abstract: Activation of the aryl hydrocarbon receptor (AhR) by immunosuppressive ligands promotes the development of regulatory T (Treg) cells. Although AhR‐induced Foxp3 + Treg cells have been well studied, much less is known about the development and fate of AhR‐induced Type 1 Treg (AhR‐Tr1) cells. In the current study, we identified the unique transcriptional and functional changes in murine CD4 + T cells that accompany the differentiation of AhR‐Tr1 cells during the CD4 + T‐cell‐dependent phase of an allospecific cytotoxic T lymphocyte (allo‐CTL) response. AhR activation increased the expression of genes involved in T‐cell activation, immune regulation and chemotaxis, as well as a global downregulation of genes involved in cell cycling.  Increased IL‐2 production was responsible for the early AhR‐Tr1 activation phenotype previously characterized as CD25 + CTLA4 + GITR + on day 2. The AhR‐Tr1 phenotype was further defined by the coexpression of the immunoregulatory receptors Lag3 and Tim3 and non‐overlapping expression of CCR4 and CCR9. Consistent with the increased expression of CCR9, real‐time imaging showed enhanced migration of AhR‐Tr1 cells to the lamina propria of the small intestine and colon. The discovery of mucosal imprinting of AhR‐Tr1 cells provides an additional mechanism by which therapeutic AhR ligands can control immunopathology. Abstract : AhR activation in alloantigen‐stimulated CD4 + T cells leads to increased IL‐2 production. Excess IL‐2 drives increased expression of CD25, CTLA4 and GITR, initiating AhR‐Tr1 cell differentiation. AhR‐Tr1 cells coexpress Lag3, Tim3, and either CCR4 or CCR9, and suppress effector T cell proliferation. AhR‐Tr1 cells subsequently accumulate in mucosal tissues.